Ada Blackjack a true story of survival in the Arctic - Niven, Jennifer 1968- (Hyperion, 2003)
It was controversial explorer Vilhjalmur Stefansson who sent four young men and Ada Blackjack into the far North to colonize desolate, uninhabited Wrangel Island. Only two of the men had set foot in the Arctic before. They took with them six months' worth of supplies on Stefansson's theory that this would be enough to sustain them for a year while they lived off the land itself. But as winter set in, they were struck by hardship and tragedy. As months went by and they began to starve, they were forced to ration their few remaining provisions. When three of the men made a desperate attempt to seek help, Ada was left to care for the fourth, who was too sick to travel. Soon after, she found herself totally alone. Upon Ada's miraculous return after two years on the island, the international press heralded her as the female Robinson Crusoe. Journalists hunted her down, but she refused to talk to anyone about her harrowing experiences. Only on one occasion -- after being accused of a horrible crime she did not commit -- did she speak up for herself. All the while, she was tricked and exploited by those who should have been her champions. Jennifer Niven, author of The Ice Master, narrates this remarkable true story, taking full advantage of a wealth of primary sources, including Ada Blackjack's never-before-seen diaries, the unpublished journals of other major characters, and interviews with Ada's second son. Filled with exciting adventure and fascinating history -- as well as extraordinary photographs -- Ada Blackjack is a gripping and ultimately inspiring tale of a woman who survived a terrible time in the wild only to face a different but equally trying ordeal back in civilization